Hydrolagus mccoskeri sp. nov., a new species of chimaeroid fish from the Galápagos Islands (Holocephali: Chimaeriformes: Chimaeridae) - Barnett, Lewis A.k.; Didier, Dominique A.; Long, Douglas J.; Ebert, David A. (Zootaxa, 2006)
A new species of chimaeroid, Hyd rolagus mccosker i sp. nov., is described from the Galápag os Islands. This species represents the second member of the family Chimaeridae known from the eastern equatorial Pacific. It can b e distinguis hed from its congeners by a combination of the following characters: small head with short, blunt snout; preopercu lar and oral lateral line canals branching from the same node off the infraorbital canal and sharing a short common b ranch; dorsum medium brown with numerous narrow, shar ply delineated circular and elongate white blotches; ventrum white to tan with extremely fine brown mottl ing. The species is compared to Hyd rolagus n ovaezealandiae and Hyd rolagus colliei , the most similar congeners in color pattern and morphology.